A Small Place: Education in Rural Tasmania - Corbett, Michael; Roberts, Philip (Australian and International Journal of Rural Education, 2017)
The field of rural education has consistently demonstrated that spatial disadvantage has material dimensions related to distance from urban nerve centres that contain services. In turn, distance from urban services entwines with multiple dimensions of social privilege and disadvantage to create specific, more or less place-based, rural, regional and remote cultural geographies. This is a problem that has historically been addressed in a number of ways, including distance-mitigation incentives to a range of system actors such as teachers, principals, students, and parents. In Tasmania, an island state to the south of the mainland Australian continent, the idea that young people have a right to a reasonably accessible, nationally and internationally normative education in their own communities, has only relatively recently been accepted. There is now a persistent, indeed insistent, multi-sectoral call for cultural change in Tasmanian regarding access to education. At this writing the state government has committed to extending all high schools which are defined as years 7-10 facilities, to offer years 11 and 12 programming by 2022 (Street, 2017). Some of this discourse responds to the positioning of Tasmania itself as a 'wicked problem' (West, 2013; Cranston et al, 2014). Notably, this discourse related to rural Tasmania echoes similar thinking about social and economic development in advanced capitalist societies around the world.